The Effect of Using Rehabilitative Exercises to Increase the Flexibility of Wrist Joint for Junior Boxing Players - Dr. Safaa Abdul-wahab Dr. Dunia (physical education and sport sciences college for women/ Baghdad University, 2019)
The application of rehabilitation exercises to accelerate the healing and get rid of pain because it provides the infected tissues with suitable means to return to its normal condition, and the speed of blood arrival to the injured place, which helps to feed the infected tissues and raise the temperature of the surrounding tissues to get rid of dead and damaged tissues and damaged and calcification by injury, which helps to increase the flexibility of muscles and joints and to increase high nutrient access processes to build damaged tissue and return to normal movement as soon as possible.       Rehabilitation exercises combines between physical exercises and other means of treatment and sauna baths to restore the level of ideal performance. So rehabilitation is an important aspect of treatment and the selection of inappropriate method for the type of injury and its force can affect the speed of recovery and then return to the stadiums as soon as possible. It has been showed through clinical tests that the return of the player to the practice of completing the appropriate rehabilitation approach can lead to recurrence of injury in the future. The importance of research is to identify the effect of using flexibility exercises in restoring normal movement to the wrist joint.      The research problem is the lack and not using exercises for stretching and flexibility of the wrist joint after a joint injury due to incorrect punching during the training on the bags of boxing. This leads to a restriction in the movement of the wrist as a result of injury and weakness of muscles moving the wrist. The researchers also found the following results: the rehabilitation exercises helped to increase the movement range by removing the calcification and increasing the blood contained in the joint and increasing flexible working muscles which help to move the wrist joint.